Analytical Method Validation for Fexofenadine Hydrochloride and Montelukast Sodium in Film-Coated Tablets by RP-HPLC Method - E. Leelavathy, S.M. Shaheedha, M. Shamshath Begum, Vasundhara Saxena (Journal of Neonatal Surgery, 2025)
The present study aims to develop and validate a simple, accurate, and robust Reverse Phase High Performance Liquid Chromatography (RP-HPLC) method for the simultaneous estimation of Fexofenadine Hydrochloride and Montelukast Sodium in a film-coated tablet formulation (Emlukast FX). These two active pharmaceutical ingredients (APIs) are commonly used in the treatment of seasonal allergic rhinitis and asthma, making their combined quality assessment essential in pharmaceutical dosage forms. The chromatographic analysis was performed using a Shimadzu LC2010CHT system with UV detection at 260 nm, utilizing a Phenomenex Luna C18 column (250 × 4.6 mm, 5 μm) at 25°C. The mobile phase consisted of a buffer (ammonium acetate adjusted to pH 5.5 with glacial acetic acid), acetonitrile, and methanol in the ratio of 12:55:33 (v/v/v) with a flow rate of 1.0 mL/min. The method was validated according to ICH Q2(R1) guidelines and demonstrated excellent specificity, linearity, precision, accuracy, robustness, and system suitability for both drugs. The % RSD for replicate injections was within acceptable limits (<2.0%), and recovery studies yielded results between 98% and 102%, confirming the method’s accuracy. The developed method can be successfully employed for routine quality control analysis of Fexofenadine and Montelukast in combined tablet dosage forms.